Hong Kong anti-human trafficking framework: what lessons can be learned from Europe? - Lo, Noble Po-kan (Frontiers in Sociology, 2024)
This article examines the regulatory framework related to human trafficking in Hong Kong and identifies its deficiencies as the lack of an accepted internationally compliant definition of trafficking and the absence of any specific criminal offence of trafficking as a result. The article compares the approach taken in Hong Kong to efforts undertaken in Europe by the Council of Europe, the UK, and the European Union and identifies several lessons from the European experience that could help rectify failures observed in Hong Kong. In particular, effective combatting of human trafficking requires not only a definition of the offence that recognises the essential elements—an “act,” a “means,” and a “purpose” of exploitation—but also the establishment of sufficient state institutions and agencies dedicated to identifying and protecting trafficking victims. Without the detection of trafficking victims, criminals engaged in the act of trafficking perceive their chances of being caught and prosecuted as low and operate with impunity. This necessitates the adoption of a consistent and readily identifiable criminal offence of “trafficking” aligned with the approach taken by the Palermo Protocol, just as the EU and UK have done.